At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

Given that [tex]\(x - 3 + \sqrt{y + 2} = -1 + \sqrt{3}\)[/tex], find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex].

Sagot :

Sure, let's solve the given equation step by step:

The given equation is:
[tex]\[ x - 3 + \sqrt{y + 2} = -1 + \sqrt{3} \][/tex]

### Step 1: Rearrange the equation to isolate \(\sqrt{y+2}\)

First, we want to isolate the term involving the square root. Let's move \(x - 3\) to one side and \(-1 + \sqrt{3}\) to the other side:
[tex]\[ \sqrt{y + 2} = -1 + \sqrt{3} - (x - 3) \][/tex]
[tex]\[ \sqrt{y + 2} = \sqrt{3} - x + 2 \][/tex]

### Step 2: Solve for \(x\)

To solve for \(x\), we can set it as:
[tex]\[ x = 3 - 1 + \sqrt{3} \][/tex]
[tex]\[ x = 2 + \sqrt{3} \][/tex]

### Step 3: Simplify the equation for \(y\)

Substitute \(x = 2 + \sqrt{3}\) back into the equation.
[tex]\[ \sqrt{y + 2} = \sqrt{3} - (2 + \sqrt{3}) + 2 \][/tex]

This simplifies to:
[tex]\[ \sqrt{y + 2} = \sqrt{3} - 2 - \sqrt{3} + 2 \][/tex]
[tex]\[ \sqrt{y + 2} = 0 \][/tex]

Square both sides to eliminate the square root:
[tex]\[ y + 2 = 0 \][/tex]
[tex]\[ y = -2 \][/tex]

### Step 4: Conclusion

The value of \(x\) is:
[tex]\[ x = 2 + \sqrt{3} \][/tex]

The value of \(y\) is:
[tex]\[ y = -2 \][/tex]

Thus, the final solution is:
[tex]\[ x = 3.73205080756888 \][/tex]
[tex]\[ y = -2 \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.